What is the role of Emerging Asia in global oil prices? - Marko Melolinna (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
This paper studies the effects of demand shocks caused by Emerging Asian (EMA) countries on oil prices over the past two decades, using vector autoregression models. The analysis builds on previous work done on identifying different types of oil shocks using structural time series methods. However, uniquely, this paper introduces a commodity demand indicator for EMA economies that is based on data independent of oil production and consumption data, thus properly accounting for oil demand pressures stemming from macroeconomic conditions in the EMA economies and the rest of the world. The analysis strongly suggests that EMA demand shocks have had a persistent and statistically significant effect on the level and variation of global oil prices over the past two decades. This result differs from some of the previous literature and hence proves that the choice of oil demand indicator in an oil-market VAR makes a material difference for the results. Furthermore, tentative evidence suggests that the effect of EMA demand is mainly driven by demand dynamics in China. The results of the benchmark model are robust to different sample periods and to variations in the definition of the oil demand indicators, as well as to an alternative identification strategy based on sign restrictions. Publication
URN:NBN:fi:bof-201411073149
Keywords: C32; E32; Q43; 330; macroeconomic shocks; oil markets; sign restrictions; vector autoregression